La défense du paradis fiscal suisse avant la Seconde Guerre mondiale une histoire internationale - Farquet, Christophe (Editions Alphil Presses universitaires suisses, 2016)
This book examines how Swiss leaders reached a deal with international pressures that appeared after the First World War, preventing the placement of foreign capital flight in Switzerland. A result of research on unpublished sources, from both Swiss and European archives, this book renews aware-ness of the history of the Swiss financial center and international economic relations during the first half of the 20th century.